Antimicrobial Stewardship at Birth in Preterm Infants: Not Just About a Decrease!. Issue 5 (8th April 2022) - Stritzke, Amelie; Tierney, Anne; Keister, Faith; Srivastava, Ankur; Dersch-Mills, Deonne; Hamilton, Claire; Lodha, Abhay; Abou Mehrem, Ayman
Abstract : Background: Early-onset sepsis results in increased morbidity and mortality in preterm infants. Antimicrobial Stewardship Programs (ASPs) address the need to balance adverse effects of antibiotic exposure with the need for empiric treatment for infants at the highest risk for early-onset sepsis. Methods: All preterm infants <34 weeks gestational age born during a 6-month period before (January 2017–June 2017) and a 6-month period after (January 2019–June 2019) implementation of ASP in May 2018 were reviewed. The presence of perinatal sepsis risk factors, eligibility for, versus treatment with initial empiric antibiotics was compared. Results: Our cohort comprised 479 infants with a mean of 30 weeks gestation and birth weight of 1400 g. Demographics were comparable, with more Cesarean section deliveries in the post-ASP cohort. Any sepsis risk factor was present in 73.6% versus 68.4% in the pre- versus post-ASP cohorts ( P = 0.23). Fewer infants were treated with antibiotics in the later cohort (60.4%) compared with the earlier cohort (69.7%; P = 0.04). Despite the presence of risk factors (preterm labor in 93% and rupture of membranes in 60%), 42% of infants did not receive initial antibiotics. Twenty percent with no perinatal sepsis risk factors were deemed low-risk and not treated. Conclusions: Implementation of a neonatal ASP decreased antibiotic initiation at birth. Antibiotic use decreased (appropriately) in the subgroup with no perinatal sepsis risk factors. Of concern, some infants were not treated despite risk factors, such as preterm labor/rupture of membrane. Neonatal ASP teams need to be aware of potentially unintended consequences of their initiatives.